Insecticidal effect of nanoencapsulated essential oils from Zanthoxylum rhoifolium (Rutaceae) in Bemisia tabaci populations Author links open overlay panel - Christofoli, Marcela; Costa, Eliangela Cristina Candida; Bicalho, Keylla U.; Domingues, Vanessa de Cássia; Peixoto, Márcio Fernandes; Alves, Cassia Cristina Fernandes; Araújo, Wagner L.; Cazal, Cristiane de Melo (Industrial Crops and Products, 2015)
The purpose of this study was to develop and characterize biodegradable nanospheres containing essential oils from Zanthoxylum rhoifolium leaves and evaluate its insecticidal effect in Bemisia tabaci populations. The essential oil from Z. rhoifolium leaves exhibited an average yield of 0.03% and presented β-elemene (31.26%), D-germacrene (18.16%), β-caryophyllene (12.09%), δ-elemene (7.63%), β-cedrene (6.69%), bicyclogermacrene (4.57%) and E-caryophyllene (3.63%) as main components. The PCL nanospheres containing this essential oil exhibited encapsulation efficiency higher than 96%, pH close to 5, particle diameter smaller than 500 nm and zeta potential values of approximately −20 mV. The in vitro release profile was characteristic of biphasic release, i.e., a fast initial release, followed by slow release for 12 h or more. The biological assay results were also significant and as such both the in natura and nanoencapsulated essential oils resulted in reductions as high as 95% in the number of eggs and nymphs compared with our control. Collectively these results suggest that both in natura and nanoencapsulated essential oils from Z. rhoifolium leaves can potentially be used in B. tabaci control in association with integrated pest management practices.
Keywords: Essential oil; Nanotechnology; Poly-ϵ-caprolactone